Examining the effect of dividend policies on shareholders of publicly listed companies in Singapore - Tan, Si Ying (2011)
This study delves into the analysis of shareholders’ preferences for different dividend policies, namely cash and stock dividends. Shareholders of publicly listed companies in Singapore will be examined by varying the dividend policies and identifying whether any abnormal returns exist. Company-specific factors will also be taken into account for their effect on stock prices, as well as how each of them contributes to the announcement effect.